Unethical Decision Making and Sleep Restriction: Experimental Evidence - David L. Dickinson; David Masclet (Institute of Labor Economics (IZA), 2021)
Recent examinations into the cognitive underpinnings of ethical decision making has focused on understanding whether honesty is more likely to result from deliberative or unconscious decision processes. We randomly assigned participants to a multi-night sleep manipulation, after which they completed 3 tasks of interest: imperfectly identifiable dishonesty (the Coin Flip task), identifiable dishonesty (the Matrix task), and anti-social allocation choices (the Money Burning game). We document the validity of the sleep protocol via significantly reduced nightly sleep levels (objectively measured using validated instrumentation) and significantly higher sleepiness ratings in the sleep-restricted (SR) group compared to the well-rested (WR) group. We report that money burning decisions are not statistically different between SR and WR participants. However, regarding honesty, we find significant and robust effects of SR on honesty. In total, given the connection between sleepiness and deliberation, these results add to the literature that has identified conditions under which deliberation impacts ethical choice. When dishonesty harms an abstract "other" person (e.g., the researcher's budget), reduced deliberation more likely increases dishonesty compared to when harm is done to someone at closer social distance (e.g., another subject).
Keywords: C91; D91; D63; 330; ethical choice; dishonesty; antisocial behavior; sleep